Quantifying Contributions of External Drivers to the Global Ionospheric State - Xing Meng; Olga P. Verkhoglyadova (Space Weather)
Abstract To advance our understanding of the global response of the ionospheric total electron content (TEC) to various external drivers, we apply entropy‐based information theory to quantify contributions of solar, interplanetary, and lower atmospheric drivers to the global ionospheric state described by the Global Ionospheric Map (GIM). By computing normalized transfer entropy on 18 years of GIM TEC, F10.7, solar wind, and lower atmospheric data, we obtain the predictive information transfer from the present drivers to the global ionospheric state at various future times. We find that the solar extreme ultraviolet (EUV) irradiance dominates the information transfer within 3 days into the future, while the lower atmospheric migrating tidal sources dominate beyond 3 days into the future. The maximum information transfer from individual drivers reveals the maximum contributions from the drivers to the global ionospheric state. Among all drivers considered, the lower atmospheric migrating tidal sources contribute most. The solar EUV irradiance and tropospheric deep convection are secondary drivers with comparable contributions at about half of the contribution from migrating tidal sources. The interplanetary driving contributes the least to the global ionospheric state during both geomagnetic storm and quiet time, even though the contribution from the interplanetary magnetic field can enhance four to six times during geomagnetic storm time than quiet time.